Web-based learning support systems: adaptability and intelligence - Kurlavičius, Algimantas (Lietuvos matematikos rinkinys, 2004)
Features of e-tutoring and e-learning systems and main tendencies of their development are analyzed. Conception of Web-B ased Learning Support Systems is discussed. The emphasis is laid on the main weaknesses of e-learning systems — insufficient contextual support, insufficient flexibility and adaptation. The impact of software agents and connected technologies on the flexibility of e-learning systems as well as possibilities of software agents’ application are reviewed. Structure of Intellectual Web-Based Learning Support System of many agents, which guarantees flexible and adaptive individual learning support environment is introduced. Perspectives of such systems are reviewed. The suggestions for the increase of e-learning support efficiency are presented.